Establishing Cardiac Surgery in Eastern Nepal: Early Results - Jaiswal, Lokesh Shekher; Prasad, Jagat Narayan; Shah, Prashant; Pandit, Narendra (Journal of Nepal Health Research Council, 2018)
Background: Only few dedicated cardiac centres provide cardiac surgery service in Nepal. We are the only government affiliated centre outside the capital providing this service. In this study, we aim to present our early results of cardiac surgery.Methods: This retrospective study was conducted at B P Koirala Institute of Health Sciences with objective of analysing the early results of cardiac surgery in the patients operated from July 2016 to March 2017.The data were analysed for patient demographics, type of surgery and cardiac disease, mortality, hospital and intensive care unit stay, valve related complications.Results: Total 51 major cardiac surgeries (42 on pump and nine off pump) were performed. There were 27 (53%) males and 24 (47%) females with median age of 36 years (range: 1 to 70 years). The cardiac diseases consisted of 28 rheumatic heart disease, 12 congenital heart diseases, five coronary artery disease, five chronic constrictive pericarditis and one left atrial myxoma. The mean cardiopulmonary bypass and cross clamp times were 106 ±35 and 80±26 minutes respectively. The mean intensive care unit and hospital stay was 4±2 and 8±3 days respectively. Two (4%) patients required re-exploration for mediastinal bleeding. There was no prosthetic valve thrombosis or infection.Two patients (4%) had superficial wound infections.There were four (7.8%) in hospital mortalities. Remaining 47 patients (91.8%) are in NYHA class I aftermean follow up duration of five months.Conclusions: Our early result of cardiac surgery is encouraging and has established the safety and feasibility of starting open heart surgery in other parts of Nepal.